STAGES OF PLANNING THE DEVELOPMENT OF AN EDUCATIONAL INSTITUTION (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
In this article, the author compiled methodological instructions for managing an educational institution based on the general laws and principles of management. The methods of educational management are one of the methods of managing the socio-psychological environment in the conditions of a large-scale flow of information, and it is a method of targeted influence of the management subject on the management object.